Architectural roadmap development of livestock information system to support the federal ministry of agriculture. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This blueprint will include a costed roadmap for the architectural design, including data flow optimization, systems and practices for metadata management, data quality control, data warehousing, data access and exchange.